PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL KOOPERATIF TIPE ROUND TABLE DI KELAS V SEKOLAH DASAR - Levia, Trisna; Taufina, Taufina; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of narrative writing skill by using round table models at grade V student of Elementary School. The type of research is PTK by using qualitative and quantitative approach. This research was conducted at SD Negeri 29 Pitameh, Padang city with a total of 20 students consisting of 8 male students and 12 female students. The result of the narrative writing skill in the pre-writing at cycle I 88,13 (SB) increases on cycle II 91,25 (SB). The writing phase in the first cycle 72,52 (B), increased in the second cycle 85 (SB), the post-writing phase cycle I 70,83 (B) increases in cycle II 90 (B).  Keywords: Increased, narrative writing, round table model.